Exploring compassionate care in rehabilitation among individuals who are involved with the criminal-legal system with traumatic brain injury: A scoping review - Martina Rubino; Caelin Mason; Giacomo Campo; Vincy Chan (PLoS ONE, 2026)
Traumatic brain injury (TBI) is disproportionately prevalent among individuals who are involved with the criminal-legal system and can impact one’s ability to critically think and emotionally regulate, thereby increasing risk of aggressive behaviour and recidivism. Considering and providing compassionate care can improve healthcare experiences and outcomes for this population. This scoping review aimed to answer the question: “To what extent is compassionate care considered or provided in rehabilitation for individuals who are involved with the criminal-legal system with TBI?” A systematic search through MEDLINE, Embase, APA PsycINFO, Cochrane Central Register, Nursing and Allied Health Premium, Criminal Justice Abstracts, CINAHL Complete, and Applied Social Sciences Index & Abstracts was established, and articles that met predetermined inclusion criteria were identified. A descriptive numerical summary and qualitative analytical techniques were applied to analyse the data. Twenty-five articles met the inclusion criteria and 24% (n = 6) of included articles were identified to provide/consider compassionate care through awareness of suffering, judgement and consideration, and motivation to alleviate suffering in rehabilitation programs, interventions, or services provided by healthcare providers or professional disciplines. While findings indicate dominance of Western contexts and a lack of routine consideration and/or provision of compassionate care, it highlights the following opportunities to integrate compassionate care in rehabilitation programs or services for those who intersect the criminal-legal system with TBI: (1) routine TBI and criminal-legal system-related education and TBI screening to increase awareness of patient suffering, (2) person-centred frameworks to address judgement and consideration of patients’ suffering, and (3) establish relationships between patients and service providers and monitor progress throughout rehabilitation to alleviate patient suffering. Research on the role of compassionate care in rehabilitation outcomes, how compassionate care may be routinely integrated, and its impact (positive or negative) on individuals are encouraged. Research globally is also encouraged, as many of the included articles/studies in this review were published in Western countries, with most of them originating from the United States. As such, findings from this review may represent a Western perspective on compassionate care and may not be generalizable to other countries.